Striatum-Mediated Deficits in Stimulus-Response Learning and Decision-Making in OCD - Hiebert, Nole M.; Lawrence, Marc R.; Ganjavi, Hooman; Watling, Mark; Owen, Adrian M.; Seergobin, Ken N.; MacDonald, Penny A. (Frontiers in Psychiatry, 2020)
Obsessive compulsive disorder (OCD) is a prevalent psychiatric disorder characterized by obsessions and compulsions. Studies investigating symptomatology and cognitive deficits in OCD frequently implicate the striatum. The aim of this study was to explore striatum-mediated cognitive deficits in patients with OCD as they complete a stimulus-response learning task previously shown to differentially rely on the dorsal (DS) and ventral striatum (VS). We hypothesized that patients with OCD will show both impaired decision making and learning, coupled with reduced task-relevant activity in DS and VS, respectively, compared to healthy controls. We found that patients with OCD (n=14) exhibited decision-making deficits and learned associations slower compared to healthy age-matched controls (n=16). Along with these behavioural deficits, OCD patients had reduced task-relevant activity in DS and VS, compared to controls. This study reveals that responses in DS and VS are altered in OCD, and sheds light on the cognitive deficits and symptoms experienced by patients with OCD.